A Comparative Study Of Internet Addiction Among Higher Secondary School Students Of District Anantnag - Firdose Ahmad Mir; Bilal Ahmad Shah; Ilyas Ahmad Rather; Mohd Arif Hussain Bhat (Elementary Education Online, 2023)
This research paper explores the phenomenon of internet addiction among higher secondary school students. The study aims to investigate the prevalence and nature of internet addiction among secondary school students of district Anantnag. The study which was descriptive in nature was conducted on 300 higher secondary school students belonging to different private and government higher secondary schools of district Anantnag. The students were sampled by using simple random technique (Lottery Method) whereas, higher secondary schools were purposively selected. Data were collected by using a standardized tool developed by Daman Deep Kaur Gulati, Dr. Jose J. Kurisunkal and Dr. Mamta Bakliwal 2021. The data were analyzed by using Mann- Whitney test. The major finding of the study was that female students belonging to different higher secondary schools of district Anantnag are more internet addicted as compared to male students belonging to different higher secondary schools of district Anantnag.